Identificação de processos erosivos em margens de reservatório de uma usina hidrelétrica - Miranda, Fernanda Gumisson (2023)
Brazil allied with the demographic growth and the exuberance of the hydric resources in the country, directed to the sector of electric energy has invested in new enterprises directed to the generation of electric energy, through renewable sources. With this, several impacts on the environment are generated, among them the manifestation of erosive processes on the banks of reservoirs resulting from the variability in the level of operation of the reservoirs. Through the help of the bibliography, certain methodologies for monitoring erosive processes were observed, which are often based on empirical and costly methods. In view of this, the present work sought, by means of a case study, to improve field work through the application of technology directed at mapping areas. The case study comprises the initial structuring, aerial monitoring surveys, topographic surveys, and data analysis. Four aerial surveys were conducted followed by processing using the software agisoft photoscan, where it was found through the generated product orthomosaic erosive process on the margin of the reservoir of the hydroelectric power plant PCH RS-155 in the northwest of the state of Rio Grande do Sul, verifying the occurrence of an erosive process and other possible areas with susceptibility of the same, however, due to GCPs distant from the monitoring areas it succeeded in significant errors in the generation of contour lines, not making viable the estimate of soil loss from the erosive process.